2017
DOI: 10.1038/s41598-017-06699-7
|View full text |Cite
|
Sign up to set email alerts
|

Chelant Enhanced Solution Processing for Wafer Scale Synthesis of Transition Metal Dichalcogenide Thin Films

Abstract: It is of paramount importance to improve the control over large area growth of high quality molybdenum disulfide (MoS2) and other types of 2D dichalcogenides. Such atomically thin materials have great potential for use in electronics, and are thought to make possible the first real applications of spintronics. Here in, a facile and reproducible method of producing wafer scale atomically thin MoS2 layers has been developed using the incorporation of a chelating agent in a common organic solvent, dimethyl sulfox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…The extra sulfur helped to remove excess oxygen and mitigate sulfur deficit caused by organic solvent evaporation [ 39 ]. Based on this, wafer scale MoS 2 thin films were synthesized by incorporating chelating agent like ethylenediaminetetraacetic acid (EDTA) with (NH 4 ) 2 MoS 4 in DMSO solvent as a spin-coating solution, followed by heat treatment in furnace at 500–800 °C and Ar atmosphere [ 40 ]. Similarly, a series of rGO/XS 2 heterostructures (X = W, Mo, or W and Mo alloy) were synthesized by dispersing (NH 4 ) 2 WS 4 or (NH 4 ) 2 MoS 4 into a GO solution followed by thermal treatment at low temperature [ 41 ].…”
Section: Growth Routes and Mechanismsmentioning
confidence: 99%
“…The extra sulfur helped to remove excess oxygen and mitigate sulfur deficit caused by organic solvent evaporation [ 39 ]. Based on this, wafer scale MoS 2 thin films were synthesized by incorporating chelating agent like ethylenediaminetetraacetic acid (EDTA) with (NH 4 ) 2 MoS 4 in DMSO solvent as a spin-coating solution, followed by heat treatment in furnace at 500–800 °C and Ar atmosphere [ 40 ]. Similarly, a series of rGO/XS 2 heterostructures (X = W, Mo, or W and Mo alloy) were synthesized by dispersing (NH 4 ) 2 WS 4 or (NH 4 ) 2 MoS 4 into a GO solution followed by thermal treatment at low temperature [ 41 ].…”
Section: Growth Routes and Mechanismsmentioning
confidence: 99%
“…Solution-based synthesis is compatible with existing nanofabrication processes, is scalable at low cost and has already been shown to produce high quality MoS 2 films using a single source precursor such as ammonium tetrathiomolybdate (NH 4 ) 2 MoS 4 through thermal decomposition for electronic devices applications 10 . Therefore, several groups have developed approaches for large area solution-based MoS 2 synthesis via two-step thermolysis of (NH 4 ) 2 MoS 4 films coated in different ways such as dip, roll to roll and spin coating [11][12][13][14][15][16][17][18] . Spin coating of (NH 4 ) 2 MoS 4 solution in particular is highly preferable among other coating techniques due to its integration with current semiconductor technology and its ability to control the initial precursor film thickness through spinning speed as well as precursor solution concentration 13,17 .…”
mentioning
confidence: 99%
“…To overcome this issue, researchers developed different organic-precursor solution systems for spin coating to enhance the uniformity and controllability of the initial precursor film over large area and eliminate surface defects. These organic-precursor solutions systems are: DMF, n-butylamine and 2-aminoethanol 13 ; ethylenediaminetetraacetic acid (EDTA) and dimethylsulfoxide (DMSO) 16 ; and linear poly (ethylenimine), DMF and 2-aminoethanol 17 .…”
mentioning
confidence: 99%
“…Several solution-synthesized MoS 2 thin films have been applied to FETs. However, they have low average effective carrier mobility, [20,31] and are therefore not suitable for commercialization. The performance of the solution-processed MoS 2 FETs are summarized in Table II.…”
Section: Field-effect Transistors (Fets)mentioning
confidence: 99%
“…An optimized solvent mixture of DMF:n-butylamine:2-aminoethanol = 4.5:4.5:1 (v/v/v, where v represents volume) generates a uniform spin-coating of the precursor, without pinholes or dewetted regions. Ionescu et al[31] reported a spin coating technique, wherein the (NH 4 ) 2 MoS 4 precursor is dissolved into a dimethyl sulfoxide (DMSO):ethylenediaminetetraacetic acid (EDTA) co-solvent. During the spin coating, the DMSO increases the wettability between the (NH 4 ) 2 MoS 4 precursor and SiO 2 substrate, and…”
mentioning
confidence: 99%